Validation of bispyribac-sodium + clomazone, new alternative to chemical weed control in rainfed rice - Esqueda Esquivel, Valentín A.; Tosquy Valle, Oscar Hugo (Revista Mexicana de Ciencias Agrícolas, 2018)
During the rainfed cycles 2006 and 2007, four plots were established in the town of Tres Valles, Veracruz, in order to validate the experimental results obtained in weed control in rice with bispyribac-sodium + clomazone , compare their efficiency and profitability against regional treatment, and transfer knowledge of new technology to rice producers in Veracruz. The following treatments were verified: 1. Bispyribac-sodium + clomazone to 22 + 480 g ha-1 and 2. Propanil at 2 880 g ha-1, followed by propanil at 2 880 g ha-1 (regional treatment). In both cycles evaluated the control Moench [Echinochloa Colona (L.) Link] and the rice f lat sedge (Cyperus iria L.) and toxicity to rice at 20 and 50 days after application of treatments. It was also determined the yield of paddyriceandprofitabilityofthetreatments.Withbispyribac- sodium + clomazone ultimate control of E. colona was 93.5%, significantly higher than the regional treatment, while control of C. iria was similar with both treatments. With the new weed control treatment, we obtained an average yield of paddy rice of 5 305 kg ha-1, while the regional, had an average of 3 256.8 kg ha-1. The improved prof itability was obtained with bispyribac- sodium + clomazone whose benefit / cost was 1.996, while with traditional treatment, was of 1.135. The new technology was transferred to 52 people, including rice producers and technicians, through two field demonstrations.
Keywords: Cyperus iria L.; Echinochloa colona (L.) link; economic analysis; herbicide; yield